Design and Simulation of Butterfly-Shaped Filtenna with Dual Band Notch for Portable UWB Applications - Juma'a, Fatimah K.; Alnahwi, Falih M. (Iraqi Journal for Electrical and Electronic Engineering, 2021)
A compact and low cost butterfly shaped UWB filtenna with a pair of parasitic elements and a pair of slits is proposed in this work. The filtenna is supposed to be designed on a common and low-cost FR4 substrate with overall dimensions of 26mm*20mm*1.6mm .By inserting a pair of g /2( where g is waveguide wavelength ) D-shaped parasitic elements around the antenna feed line, the radiation of the 5 GHz WLAN applications is canceled to eliminated the interference . Furthermore, the rejection of the X-band satellite downlink is achieved by engraving a pair of g /4 J-shaped slits on the ground plane. The simulation results exhibits the perfect coverage of the proposed filtenna for the UWB frequency band as well as the elimination of the undesired radiation within the filtenna operating band.